Analisis Pengaruh Profitabilitas terhadap Return Saham dengan Nilai Perusahaan sebagai Variabel Moderasi: Studi Kasus pada Perusahaan Telekomunikasi di BEI pada 2018-2023 - Rahayu, Maulana Yusup; Sucipto, Agus (Jurnal Akuntansi, Keuangan, dan Manajemen, 2024)
Purpose: The purpose of this study was to test and analyse the effect of profitability on stock returns. Methodology: The research method used in this research is quantitative method. The research method used in this research is panel data regression. The sampling technique used in this research is nonprobability sampling with purposive sampling method so that the total sample is 6 telecommunication sector companies listed on the Indonesia Stock Exchange for the period 2018-2023. The analysis method used in this research is panel data regression analysis using Eviews 12. Results: The results of this study indicate that only Net Profit Margin has an influence on stock returns, while Return On Asset, and Earning Per Share have no significant effect on stock returns, and firm value interpreted by Price Book Value cannot moderate the effect of Return On Asset, Net Profit Margin, and Earning Per Share on stock returns. Limitations: The research is limited to several factors, namely the ratio of return on assets, net profit margin, earning per share, and price book value to stock profits. Besides, this research is only limited to telecommunication companies listed on the Indonesia Stock Exchange for the period 2018-2023. Contribution: This research can be used for consideration of stock investors in analysing stocks, this research can also be used as a literature reference for further research in examining stock returns.